The Effect Of Brown Sea Extract Subsitution On Chicken Sausage Afkir Quality - Rahmi Holinesti; Nurhayani Nurhayani (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
The background of this research is that there is no utilization of brown seaweed and chicken afkir. Brown seaweed is still called a useless plant along the Nirwana beach located in the Bungus area of Padang City. Chicken afkir are laying hens that are no longer productive for laying eggs because these chickens are old. This study aims to analyze the effect of 5ml, 10ml, and 15ml brown seaweed extract substitution on the quality of chicken afkir sausage in terms of  shape, color, aroma, texture and taste. This type of research is an experiment using the Randomized Complete Design method. The type of data used is primary data obtained directly from 5 trained panelists by filling in the organoleptic test format. Data analysis using ANAVA. If there is a significant effect, then proceed with the Duncan test. The results showed that there was no substitution effect of brown seaweed extract on the quality of the shape, color, aroma, texture and taste of the chicken afkir sausage. The best research results are on the use of tempe flour as much as 5% (X1) on the quality of the shape, color, aroma, texture and taste of the chicken afkir sausage.